Method of manufacturing wavelength conversion sheet
In the manufacturing process of the wavelength conversion sheet, the double-layer protective film structure and two-way ultraviolet irradiation method are used to solve the problem that traditional wavelength conversion sheets are prone to warping, and better workingability and stability are achieved.
Patent Information
- Application Number
- JP2024179752
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-20
- Filing Date
- 2024-10-15
- Publication Date
- 2025-05-02
AI Technical Summary
Traditional wavelength converter is prone to warping, resulting in poor workingability in backlit LCD monitors and cracks on the screen.
The wavelength conversion sheet manufacturing method adopts a double-layer protective film structure. By using ultraviolet light irradiation in two times during the process of forming the quantum dot-containing layer, the relationship between the accumulated amount of ultraviolet light is controlled to reduce interlayer stress and improve adhesion.
It effectively suppresses the warping phenomenon of the wavelength converter, improves its workingability and stability in the backlit liquid crystal display, and avoids cracks on the screen.
Smart Images

Figure 2025071007000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a wavelength conversion sheet. [Background technology]
[0002] The demand for liquid crystal display devices is increasing with the development of personal computers. Recently, the penetration rate of home LCD televisions has been increasing, and smartphones and tablet devices are also becoming more and more widespread. As a result, the market for liquid crystal display devices is expected to expand further. A liquid crystal display device generally comprises a color filter, a liquid crystal cell, and a backlight. A liquid crystal display device controls the intensity of light by using the shutter function of the liquid crystal layer in the liquid crystal cell, and displays images by dividing the color of each pixel into the three primary colors R, G, and B using a color filter.
[0003] Cold cathode fluorescent lamps have traditionally been used as light sources for the backlight of liquid crystal display devices. However, from the viewpoints of low power consumption and space saving, the light source for backlights is being switched from cold cathode fluorescent lamps to LEDs. The LEDs used as the light source for backlights are white LEDs, which are a combination of blue LEDs and YAG yellow phosphors. White LEDs have a broad spectral distribution of emitted wavelengths and are known as pseudo-white.
[0004] Meanwhile, in recent years, development of backlights using quantum dots, which are nanometer-sized semiconductor particles, has also been progressing. The basic configuration of a backlight using quantum dots is a combination of a light source that generates primary light, such as a blue LED that emits blue light, and quantum dots.
[0005] Quantum dots are nano-sized compound semiconductor particles, each of which is composed of a semiconductor particle with a core of CdSe and a shell of ZnS, and a ligand that covers the shell. Quantum dots have a quantum confinement effect because their particle diameter is smaller than the Bohr radius of the exciton of the compound semiconductor. Therefore, the luminous efficiency of quantum dots is higher than that of phosphors that use conventional rare earth ions as an activator, and they can achieve a high luminous efficiency of 90% or more. The emission wavelength of quantum dots is determined by the band gap energy of the quantized compound semiconductor particles, so any emission wavelength can be obtained by changing the particle size of the quantum dots. Backlights that combine these quantum dots with blue LEDs or the like are said to be capable of achieving high luminous efficiency and high color purity (for example, Patent Documents 1 and 2). Furthermore, quantum dots are used not only in backlights for liquid crystal display devices, but also in lighting, quantum dot lasers, and the like.
[0006] While quantum dots have the above-mentioned excellent characteristics, they have a problem that they are easily deteriorated by the influence of moisture, oxygen, etc. For this reason, it is preferable to protect both sides of the quantum dot-containing layer with a protective film including a barrier layer. For example, Patent Documents 3 and 4 have proposed wavelength conversion sheets in which both sides of the quantum dot-containing layer are protected with a protective film. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2012 / 132239 [Patent Document 2] JP 2015-18131 A [Patent Document 3] International Publication No. 2022 / 039013 [Patent Document 4] International Publication No. 2022 / 039015 Summary of the Invention [Problem to be solved by the invention]
[0008] However, the conventional wavelength conversion sheets of Patent Documents 3 and 4 and the like may curl. A curled wavelength conversion sheet may reduce workability when assembled into a backlight. Furthermore, a curled wavelength conversion sheet may cause cracks in the barrier layer due to the curl.
[0009] In view of the above problems, an object of the present disclosure is to provide a method for producing a wavelength conversion sheet that can suppress the occurrence of curling. [Means for solving the problem]
[0010] This disclosure provides the following [1]. [1] A method for producing a wavelength conversion sheet, comprising the following steps 1 to 4: Step 1: A step of forming a quantum dot-containing layer by applying a coating liquid for forming a quantum dot-containing layer onto a first primer layer of a first protective film for quantum dots, the first primer layer having at least a first primer layer, a first substrate, and a first barrier layer. Step 2: Irradiating the quantum dot-containing layer with ultraviolet light for the first time. Step 3: A step of obtaining a work-in-progress wavelength conversion sheet having, in this order, the first protective film for quantum dots, the quantum dot-containing layer, and the second protective film for quantum dots, by bonding the surface of the second primer layer side of the second protective film for quantum dots, which has at least a second primer layer, a second substrate, and a second barrier layer, to the quantum dot-containing layer. Step 4: A step of irradiating the quantum dot-containing layer of the in-process product with ultraviolet light for a second time, with the proviso that the relationship of the integrated amount of ultraviolet light for the first time < the integrated amount of ultraviolet light for the second time is satisfied. Effect of the Invention
[0011] The method for producing a wavelength conversion sheet according to the present disclosure can suppress curling of the wavelength conversion sheet. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a cross-sectional view showing an embodiment of a wavelength conversion sheet obtained by the method for producing a wavelength conversion sheet according to the present disclosure. [Diagram 2] FIG. 13 is a diagram for explaining a curled state. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, embodiments of the present disclosure will be described. In this specification, the notation "AA to BB" means from AA to BB.
[0014] [Method of manufacturing wavelength conversion sheet] The method for producing a wavelength conversion sheet of the present disclosure includes the following steps 1 to 4. Step 1: A step of forming a quantum dot-containing layer by applying a coating liquid for forming a quantum dot-containing layer onto a first primer layer of a first protective film for quantum dots, the first primer layer having at least a first primer layer, a first substrate, and a first barrier layer. Step 2: Irradiating the quantum dot-containing layer with ultraviolet light for the first time. Step 3: A step of obtaining a work-in-progress wavelength conversion sheet having, in this order, the first protective film for quantum dots, the quantum dot-containing layer, and the second protective film for quantum dots, by bonding the surface of the second primer layer side of the second protective film for quantum dots, which has at least a second primer layer, a second substrate, and a second barrier layer, to the quantum dot-containing layer. Step 4: A step of irradiating the quantum dot-containing layer of the in-process product with ultraviolet light for a second time, with the proviso that the relationship of the integrated amount of ultraviolet light for the first time < the integrated amount of ultraviolet light for the second time is satisfied.
[0015] FIG. 1 is a cross-sectional view showing an embodiment of a wavelength conversion sheet 200 obtained by the method for producing a wavelength conversion sheet according to the present disclosure. The wavelength conversion sheet 200 in Fig. 1 has a first protective film for quantum dots 10, a quantum dot-containing layer 30, and a second protective film for quantum dots 20 in this order. In Fig. 1, the first protective film for quantum dots 10 has a first primer layer 11, a first barrier layer 13, and a first substrate 12, and further has a first adhesive layer 14 and a protective substrate 15 for the first barrier layer. In Fig. 1, the second protective film for quantum dots 20 has a second primer layer 21, a second barrier layer 23, and a second substrate 22. In Fig. 1, the first primer layer 11 and the second primer layer 21 are each in contact with the quantum dot-containing layer 30.
[0016] Fig. 1 is a schematic cross-sectional view. That is, in Fig. 1, the scale of each layer constituting the wavelength conversion sheet 200 is schematic for ease of illustration, and differs from the actual scale. The same is true for Fig. 2. The wavelength conversion sheet is not limited to the layer structure of Fig. 1.
[0017] 2 is a diagram for explaining a curled state of the wavelength conversion sheet, in which the wavelength conversion sheet has a curled shape with both ends raised. The degree of curl of the wavelength conversion sheet 200 is determined according to the following steps X1 to X4. X1: The wavelength conversion sheet is cut into a sample 201 having a size of 100 mm×100 mm. X2: The sample 201 is placed on a horizontal stand 500 with the surface of the first quantum dot protective film facing the stand 500. The height h of each of the four corners of the sample 201 above the horizontal stand 500 is measured. The average value Ave1 of the top two heights of the four points is calculated. The larger the Ave1 value, the greater the degree of curling in which the first quantum dot protective film side is convex. X3: The sample 201 is placed on a horizontal stand 500 with the surface of the second quantum dot protective film facing the stand 500. The height h of each of the four corners of the sample 201 above the horizontal stand 500 is measured. The average value Ave2 of the top two heights of the four points is calculated. The larger the Ave2 value, the greater the degree of curling in which the second quantum dot protective film side is convex. It can be said that the smaller both X4:Ave1 and Ave2 are, the more the curl of the wavelength conversion sheet is suppressed.
[0018] When the larger of Ave1 and Ave2 is defined as Ave(max), Ave(max) is preferably 10.0 mm or less, more preferably 8.0 mm or less, and even more preferably 5.0 mm or less. By setting Ave1 and Ave2 to 10.0 mm or less, the wavelength conversion sheet can be easily incorporated into a backlight and a liquid crystal display device, and by setting Ave1 and Ave2 to 10.0 mm or less, it is possible to easily prevent cracks from occurring in the first barrier layer and the second barrier layer. As can be understood from the above description, in this specification, the term "suppressing curling" is not limited to completely eliminating curling, but is a concept that includes reducing the degree of curling.
[0019] The method for producing a wavelength conversion sheet of the present disclosure must include steps 1 to 4. Each step will be described below. The embodiment of the material used in steps 1 and 3 will be described after step 4.
[0020] <Process 1> Step 1 is a step of forming a quantum dot-containing layer by applying a coating liquid for forming a quantum dot-containing layer onto a first primer layer of a first protective film for quantum dots, the first primer layer having at least a first primer layer, a first substrate, and a first barrier layer.
[0021] In step 1, a quantum dot-containing layer is formed by applying a coating liquid for forming a quantum dot-containing layer onto the first primer layer of the first protective film for quantum dots. Therefore, the first primer layer and the quantum dot-containing layer are in contact with each other.
[0022] The coating liquid for forming the quantum dot-containing layer contains materials constituting the quantum dot-containing layer, such as quantum dots and a binder resin, and an optional additive component, such as a dilution solvent, etc. The coating liquid for forming the quantum dot-containing layer preferably contains an ultraviolet-curable resin composition as a binder component. The coating liquid for forming the quantum dot-containing layer may be applied onto the primer layer by a general-purpose coating method such as bar coating, die coating, or gravure coating.
[0023] <Process 2> Step 2 is a step of irradiating the quantum dot-containing layer with ultraviolet light for the first time.
[0024] In steps 2 and 4, a general-purpose device can be used as the device for irradiating ultraviolet rays. A general-purpose lamp such as a high-pressure mercury lamp or a UV-LED can be used as the lamp for emitting ultraviolet rays. In steps 2 and 4, the ultraviolet irradiation is preferably carried out in a nitrogen atmosphere. In step 2, it is preferable to irradiate the quantum dot-containing layer with ultraviolet light.
[0025] In step 2, it is preferable to adjust the cumulative amount of ultraviolet light so as not to completely cure the ultraviolet-curable resin composition in the quantum dot-containing layer. The cumulative amount of ultraviolet light in step 2 varies depending on the thickness of the quantum dot-containing layer and cannot be generally determined, but is preferably 10 mJ / cm 2 More than 2000mJ / cm 2 It is preferable that the concentration is less than 20 mJ / cm 2 More than 1500mJ / cm 2 More preferably, it is 30 mJ / cm or less. 2 More than 1000mJ / cm 2 It is even more preferable that:
[0026] <Process 3> Step 3 is a step of obtaining a work-in-progress wavelength conversion sheet having, in this order, the first protective film for quantum dots, the quantum dot-containing layer, and the second protective film for quantum dots, by bonding the surface of the second primer layer side of the second protective film for quantum dots, which has at least a second primer layer, a second substrate, and a second barrier layer, to the quantum dot-containing layer.
[0027] In step 3, the surface of the second protective film for quantum dots on the side of the second primer layer is attached to the quantum dot-containing layer, so that the second primer layer and the quantum dot-containing layer come into contact with each other. The bonding in step 3 can be carried out using a general-purpose lamination method.
[0028] The surface of the second primer layer side of the second protective film for quantum dots and the quantum dot-containing layer can be bonded together, for example, by utilizing the tack of the uncured ultraviolet-curable resin composition of the quantum dot-containing layer. For this reason, it is preferable not to completely cure the ultraviolet-curable resin composition in the quantum dot-containing layer during the first ultraviolet irradiation in step 2.
[0029] <Step 4> Step 4 is a step of irradiating the quantum dot-containing layer of the in-process product with ultraviolet light for the second time, provided that the relationship of the integrated amount of ultraviolet light for the first time < the integrated amount of ultraviolet light for the second time is satisfied.
[0030] The integrated light amount of the ultraviolet light in step 4 is not particularly limited as long as it satisfies the relationship of integrated light amount of the first ultraviolet light < integrated light amount of the second ultraviolet light. The integrated light amount of the ultraviolet light in step 4 varies depending on the thickness of the quantum dot-containing layer, etc., so it cannot be generalized, but it is preferably 100 mJ / cm 2 More than 5000mJ / cm 2 It is preferable that the concentration is less than 150 mJ / cm 2 More than 4000mJ / cm 2 More preferably, it is 200 mJ / cm or less. 2More than 3000mJ / cm 2 It is even more preferable that: In step 4, ultraviolet light may be irradiated from the first protective film for quantum dots side, but it is preferable to irradiate ultraviolet light from the second protective film for quantum dots side.
[0031] In the method for producing a wavelength conversion sheet of the present disclosure, ultraviolet rays are irradiated in each of steps 2 and 4. That is, in the method for producing a wavelength conversion sheet of the present disclosure, the ultraviolet curable resin composition in the quantum dot-containing layer is cured in two separate steps. Furthermore, in the method for producing a wavelength conversion sheet of the present disclosure, as specified in step 4, ultraviolet rays are irradiated so as to satisfy the relationship of the integrated light amount of the first ultraviolet ray<the integrated light amount of the second ultraviolet ray. The method for producing a wavelength conversion sheet according to the present disclosure irradiates the wavelength conversion sheet with ultraviolet light twice and satisfies the relationship that the integrated amount of ultraviolet light emitted in the first irradiation is less than the integrated amount of ultraviolet light emitted in the second irradiation, thereby preventing curling of the wavelength conversion sheet. The reason why the method for producing a wavelength conversion sheet according to the present disclosure can prevent curling is explained below.
[0032] First, a wavelength conversion sheet has conventionally been produced by the following steps A1 to A3 (see the examples in Patent Documents 1 and 2). Step A1: A step of forming a quantum dot-containing layer by applying a coating liquid for forming a quantum dot-containing layer onto a first primer layer of a first protective film for quantum dots, the first primer layer having at least a first primer layer, a first substrate, and a first barrier layer. Step A2: A step of obtaining a work-in-progress wavelength conversion sheet having, in this order, the first protective film for quantum dots, the quantum dot-containing layer, and the second protective film for quantum dots, by bonding the surface of the second primer layer side of the second protective film for quantum dots, which has at least a second primer layer, a second substrate, and a second barrier layer, to the quantum dot-containing layer. Step A3: A step of irradiating the quantum dot-containing layer of the in-process product with ultraviolet light.
[0033] When the wavelength conversion sheet is produced by the above steps A1 to A3, the coating liquid for forming the quantum dot-containing layer easily permeates into the first primer layer but does not easily permeate into the second primer layer. Therefore, the wavelength conversion sheet produced by the above steps A1 to A3 tends to have a relationship in which the adhesion between the second primer layer and the quantum dot-containing layer is less than the adhesion between the first primer layer and the quantum dot-containing layer. Furthermore, when the wavelength conversion sheet is manufactured by the above steps A1 to A3, the curing shrinkage of the quantum dot-containing layer proceeds all at once in step A3. When the curing shrinkage of the quantum dot-containing layer proceeds all at once, poor adhesion is likely to occur between the quantum dot-containing layer and the first primer layer, and between the quantum dot-containing layer and the second primer layer. The above-mentioned poor adhesion is more likely to occur between the quantum dot-containing layer and the second primer layer, which have weak adhesion. Therefore, in the wavelength conversion sheet manufactured by the above steps A1 to A3, the difference between the adhesion between the second primer layer and the quantum dot-containing layer and the adhesion between the first primer layer and the quantum dot-containing layer is more likely to become large. The stress caused by the contraction of the quantum dot-containing layer is easily transmitted to the side with stronger adhesion. Therefore, when a wavelength conversion sheet is produced by the above steps A1 to A3, the stress caused by the contraction of the quantum dot-containing layer is more easily transmitted to the first protective film for quantum dots than to the second protective film for quantum dots. Therefore, when a wavelength conversion sheet is produced by the above steps A1 to A3, the wavelength conversion sheet is more likely to curl convexly toward the first protective film for quantum dots.
[0034] On the other hand, the manufacturing method of the wavelength conversion sheet of the present disclosure divides the irradiation of ultraviolet rays into two times, so that the stress caused when the quantum dot-containing layer cures and shrinks can be distributed twice. Therefore, the manufacturing method of the wavelength conversion sheet of the present disclosure can easily suppress the occurrence of poor adhesion between the quantum dot-containing layer and both primer layers when the quantum dot-containing layer cures and shrinks. Furthermore, the manufacturing method of the wavelength conversion sheet of the present disclosure can easily cause a reaction at the interface between the second primer layer and the quantum dot-containing layer by satisfying the relationship of the integrated light amount of the first ultraviolet rays<the integrated light amount of the second ultraviolet rays, so that the adhesion between the second primer layer and the quantum dot-containing layer can be easily improved. On the other hand, in the case of the relationship of the integrated light amount of the first ultraviolet rays≧the integrated light amount of the second ultraviolet rays, the amount of reactive functional groups in the quantum dot-containing layer is reduced at the time of the irradiation of the second ultraviolet rays, so that the adhesion between the second primer layer and the quantum dot-containing layer cannot be improved. As described above, the method for producing a wavelength conversion sheet according to the present disclosure can easily reduce the difference between the adhesion between the second primer layer and the quantum dot-containing layer and the adhesion between the first primer layer and the quantum dot-containing layer by dividing the ultraviolet irradiation into two steps and satisfying the relationship of the integrated amount of ultraviolet light of the first step < the integrated amount of ultraviolet light of the second step. Therefore, according to the method for producing a wavelength conversion sheet according to the present disclosure, when the quantum dot-containing layer is cured, the difference between the stress transmitted to the second protective film for quantum dots and the stress transmitted to the first protective film for quantum dots can be easily reduced, and curling of the wavelength conversion sheet can be easily suppressed.
[0035] The ratio of the cumulative amount of the second ultraviolet ray to the cumulative amount of the first ultraviolet ray is preferably 2 or more and 30 or less, more preferably 3 or more and 20 or less, and even more preferably 4 or more and 10 or less. By setting the above ratio within the above range, it is possible to make it easier to reduce the difference between the adhesion strength between the second primer layer and the quantum dot-containing layer and the adhesion strength between the first primer layer and the quantum dot-containing layer, thereby making it easier to suppress curling of the wavelength conversion sheet.
[0036] In the configuration elements shown in this specification, when multiple options for the upper limit and the lower limit of the numerical value are shown, it is assumed that an embodiment is described that combines one selected from the upper limit and one selected from the lower limit. For example, the above-mentioned embodiment of the range of the integrated light amount of the second ultraviolet ray / integrated light amount of the first ultraviolet ray may be 2 to 30, 2 to 20, 2 to 10, 3 to 30, 3 to 20, 3 to 10, 4 to 30, 4 to 20, and 4 to 10.
[0037] <Protective film> The method for producing a wavelength conversion sheet of the present disclosure uses a first protective film for quantum dots and a second protective film for quantum dots. In this specification, the "first protective film for quantum dots" and the "second protective film for quantum dots" may be abbreviated as the "first protective film" and the "second protective film", respectively.
[0038] First protective film The first protective film has at least a first primer layer, a first substrate, and a first barrier layer. The first protective film may have layers other than the first primer layer, the first substrate, and the first barrier layer. Examples of layers other than the first primer layer, the first substrate, and the first barrier layer include a first adhesive layer, a first bulking substrate, a protective substrate for the first barrier layer, and a first anti-sticking layer.
[0039] Examples of the laminate structure of the first protective film include the following 1-1 to 1-12, where " / " indicates the interface between adjacent layers. 1-1: First primer layer / first substrate / first barrier layer 1-2: First primer layer / first barrier layer / first substrate 1-3: First primer layer / first substrate / first barrier layer / first adhesive layer / first bulking substrate 1-4: First primer layer / first barrier layer / first substrate / first adhesive layer / first bulking substrate 1-5: First primer layer / first substrate / first barrier layer / first adhesive layer / protective substrate for first barrier layer 1-6: First primer layer / First barrier layer / First substrate / First adhesive layer / Protective substrate for first barrier layer 1-7: 1st primer layer / 1st substrate / 1st barrier layer / 1st anti-sticking layer 1-8: 1st primer layer / 1st barrier layer / 1st substrate / 1st anti-sticking layer 1-9: 1st primer layer / 1st substrate / 1st barrier layer / 1st adhesive layer / 1st bulking substrate / 1st anti-sticking layer 1-10: 1st primer layer / 1st barrier layer / 1st substrate / 1st adhesive layer / 1st bulking substrate / 1st anti-sticking layer 1-11: 1st primer layer / 1st substrate / 1st barrier layer / 1st adhesive layer / protective substrate for 1st barrier layer / 1st anti-sticking layer 1-12: 1st primer layer / 1st barrier layer / 1st substrate / 1st adhesive layer / 1st barrier layer protective substrate / 1st anti-sticking layer
[0040] The first protective film may have a first bulking substrate to more easily suppress curling. In the first protective film, the first bulking substrate is preferably disposed at a position farther from the first primer layer than the first substrate and the first barrier layer. The first bulking substrate is preferably formed on the first substrate or the first barrier layer via a first adhesive layer. By forming the first bulking substrate on the first substrate or the first barrier layer via the first adhesive layer, the stress of the quantum dot-containing layer is alleviated by the first adhesive layer, making it easier to suppress curling.
[0041] The first protective film may have a protective substrate for the first barrier layer in order to more easily suppress curling. In the first protective film, the protective substrate for the first barrier layer is preferably disposed at a position farther from the first primer layer than the first substrate and the first barrier layer. The protective substrate for the first barrier layer is preferably formed on the first substrate or the first barrier layer via a first adhesive layer. The protective substrate for the first barrier layer and the first adhesive layer are preferably formed so as to be peelable from the first substrate or the first barrier layer. By forming the protective substrate for the first barrier layer on the first substrate or the first barrier layer via the first adhesive layer, the stress of the quantum dot-containing layer is relaxed by the first adhesive layer, making it easier to suppress curling.
[0042] Second protective film The second protective film has at least a second primer layer, a second substrate, and a second barrier layer. The second protective film may have layers other than the second primer layer, the second substrate, and the second barrier layer. Examples of layers other than the second primer layer, the second substrate, and the second barrier layer include a second adhesive layer, a second bulking substrate, a protective substrate for the second barrier layer, and a second anti-sticking layer.
[0043] Examples of the layered structure of the second protective film include the following 2-1 to 2-12, where " / " indicates the interface between adjacent layers. 2-1: Second primer layer / second substrate / second barrier layer 2-2: Second primer layer / Second barrier layer / Second substrate 2-3: 2nd primer layer / 2nd substrate / 2nd barrier layer / 2nd adhesive layer / 2nd bulking substrate 2-4: 2nd primer layer / 2nd barrier layer / 2nd substrate / 2nd adhesive layer / 2nd bulking substrate 2-5: Second primer layer / Second substrate / Second barrier layer / Second adhesive layer / Protective substrate for second barrier layer 2-6: Second primer layer / Second barrier layer / Second substrate / Second adhesive layer / Protective substrate for second barrier layer 2-7: 2nd primer layer / 2nd substrate / 2nd barrier layer / 2nd anti-sticking layer 2-8: 2nd primer layer / 2nd barrier layer / 2nd substrate / 2nd anti-sticking layer 2-9: 2nd primer layer / 2nd substrate / 2nd barrier layer / 2nd adhesive layer / 2nd bulking substrate / 2nd anti-sticking layer 2-10: 2nd primer layer / 2nd barrier layer / 2nd substrate / 2nd adhesive layer / 2nd bulking substrate / 2nd anti-sticking layer 2-11: 2nd primer layer / 2nd substrate / 2nd barrier layer / 2nd adhesive layer / protective substrate for 2nd barrier layer / 2nd anti-sticking layer 2-12: 2nd primer layer / 2nd barrier layer / 2nd substrate / 2nd adhesive layer / protective substrate for 2nd barrier layer / 2nd anti-sticking layer
[0044] In order to reduce the thickness of the second protective film, it is preferable that the second protective film does not have a second bulking substrate and a protective substrate for the second barrier layer.
[0045] In the wavelength conversion sheet, the layers constituting the first protective film and the layers constituting the second protective film may be arranged symmetrically or asymmetrically with respect to the quantum dot-containing layer. As an example, when the lamination structure of the first protective film is the above-mentioned 1-1 and the lamination structure of the second protective film is the above-mentioned 2-1, the layers constituting the first protective film and the layers constituting the second protective film are arranged symmetrically with respect to the quantum dot-containing layer. As another example, when the lamination structure of the first protective film is the above-mentioned 1-2 and the lamination structure of the second protective film is the above-mentioned 2-1, the layers constituting the first protective film and the layers constituting the second protective film are arranged asymmetrically with respect to the quantum dot-containing layer.
[0046] In order to facilitate the thinning of the wavelength conversion sheet, the first protective film and the second protective film are preferably used in the following combination (1) or (2), and more preferably in combination (2). (1) The first protective film has a first primer layer, a first substrate, a first barrier layer, and a first bulking substrate. The second protective film has a second primer layer, a second substrate, and a second barrier layer, but does not have a second bulking substrate or a protective substrate for the second barrier layer. (2) The first protective film has a first primer layer, a first substrate, a first barrier layer, and a protective substrate for the first barrier layer. The second protective film has a second primer layer, a second substrate, and a second barrier layer, but does not have a second bulking substrate or a protective substrate for the second barrier layer.
[0047] -Base material- Hereinafter, when simply referred to as "substrate", it means "first substrate and second substrate". The substrate is preferably a resin film that does not impair the function of the wavelength conversion sheet. The substrate may be a resin film containing one or more resins selected from polyester, triacetyl cellulose, cellulose diacetate, cellulose acetate butyrate, polyamide, polyimide, polyethersulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyether ketone, acrylic, polycarbonate, polyurethane, and amorphous olefin. Among these resin films, from the viewpoints of curl suppression, mechanical strength, dimensional stability, and heat resistance, uniaxially or biaxially stretched resin films are preferred, and biaxially stretched resin films are more preferred. The stretched resin film is preferably a polyester film. Examples of the polyester film include a polyethylene terephthalate film and a polyethylene naphthalate film.
[0048] The thickness of the substrate is preferably 5 μm or more, more preferably 8 μm or more, and even more preferably 10 μm or more. The thickness of the substrate is preferably 60 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less. The thickness of the first substrate and the thickness of the second substrate may be the same or different.
[0049] In this specification, the thickness of each layer constituting the wavelength conversion sheet is calculated by measuring the thickness at four points on an image of a cross section taken with a scanning electron microscope (SEM) and averaging the values at the four points.
[0050] In this specification, various measurements and evaluations such as curl measurement and layer thickness measurement are carried out in an indoor atmosphere with a temperature of 23° C.±5° C. and a relative humidity of 40% to 65%, unless otherwise specified. Furthermore, before carrying out various measurements and evaluations, the sample is exposed to the above atmosphere for 30 minutes to 60 minutes.
[0051] -Bulking base material- Hereinafter, when simply referred to as "bulking substrate", it means "first bulking substrate and second bulking substrate".
[0052] A protective substrate for a barrier layer, which will be described later, is a substrate that is peeled off after step 4, whereas a bulking substrate is a substrate that remains as a constituent member of the wavelength-conversion sheet even after step 4.
[0053] As the bulk-increasing substrate, a resin film that does not impair the function of the wavelength conversion sheet is preferably used. Examples of the bulk-increasing substrate include a resin film containing one or more resins selected from polyester, triacetyl cellulose, cellulose diacetate, cellulose acetate butyrate, polyamide, polyimide, polyethersulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyether ketone, acrylic, polycarbonate, polyurethane, and amorphous olefin. Among these resin films, from the viewpoints of curl suppression, mechanical strength, dimensional stability, and heat resistance, uniaxially or biaxially stretched resin films are preferred, and biaxially stretched resin films are more preferred. The stretched resin film is preferably a polyester film. Examples of the polyester film include a polyethylene terephthalate film and a polyethylene naphthalate film.
[0054] The first protective film may have a first bulking substrate to more easily suppress curling, and the second protective film may have a second bulking substrate as long as the effects of the present disclosure are not impaired.
[0055] The thickness of the bulking substrate is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more. By making the thickness of the bulking substrate 10 μm or more, the handleability of the wavelength conversion sheet can be easily improved. The thickness of the bulking substrate is preferably 200 μm or less, more preferably 150 μm or less, still more preferably 100 μm or less, and still more preferably 75 μm or less, in order to make the wavelength conversion sheet thinner.
[0056] The thickness of the first substrate and the thickness of the first bulking substrate preferably satisfy the relationship of "thickness of the first substrate < thickness of the first bulking substrate". The thickness of the second substrate and the thickness of the second bulking substrate preferably satisfy the relationship of "thickness of the second substrate < thickness of the second bulking substrate". By satisfying the above relationship, it is possible to improve the efficiency in forming a barrier layer on a substrate and to easily improve the stiffness and strength of the wavelength conversion sheet.
[0057] -Protective substrate for barrier layer- Hereinafter, when simply referred to as "protective substrate for a barrier layer", this means "protective substrate for a first barrier layer and protective substrate for a second barrier layer".
[0058] The protective substrate for the barrier layer is a substrate to be peeled off after the production of the wavelength conversion sheet. The protective substrate for the barrier layer has a role of protecting the barrier layer and improving the handleability of the protective film during the production of the wavelength conversion sheet. The protective substrate for the barrier layer is preferable in that it can make the wavelength conversion sheet thinner and can more easily suppress curling of the wavelength conversion sheet.
[0059] In the method for producing a wavelength conversion sheet of the present disclosure, when the first protective film for quantum dots further has a protective substrate for the first barrier layer, it is preferable to have a step of peeling off the protective substrate for the first barrier layer after step 4. In the method for producing a wavelength conversion sheet of the present disclosure, when the second protective film for quantum dots further has a protective substrate for the second barrier layer, it is preferable to have a step of peeling off the protective substrate for the second barrier layer after step 4.
[0060] As the protective substrate for the barrier layer, a resin film that does not impair the function of the wavelength conversion sheet is preferably used. Examples of protective substrates for barrier layers include resin films containing one or more resins selected from polyester, triacetyl cellulose, cellulose diacetate, cellulose acetate butyrate, polyamide, polyimide, polyethersulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyether ketone, acrylic, polycarbonate, polyurethane, and amorphous olefin. Among these resin films, from the viewpoints of curl suppression, mechanical strength, dimensional stability, and heat resistance, uniaxially or biaxially stretched resin films are preferred, and biaxially stretched resin films are more preferred. The stretched resin film is preferably a polyester film. Examples of the polyester film include a polyethylene terephthalate film and a polyethylene naphthalate film.
[0061] The first protective film preferably has a protective substrate for the first barrier layer to more easily suppress curling. The second protective film may have a protective substrate for the second barrier layer as long as the effects of the present disclosure are not impaired.
[0062] The thickness of the protective substrate for a barrier layer is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more. By making the thickness of the protective substrate for a barrier layer 10 μm or more, the handleability of the wavelength conversion sheet can be easily improved. The thickness of the protective substrate for a barrier layer is preferably 150 μm or less, more preferably 100 μm or less, more preferably 75 μm or less, and even more preferably 50 μm or less, in order to make the wavelength-conversion sheet thinner.
[0063] The thickness of the first substrate and the thickness of the protective substrate for the first barrier layer preferably satisfy the relationship "thickness of the first substrate<thickness of the protective substrate for the first barrier layer". The thickness of the second substrate and the thickness of the protective substrate for the second barrier layer preferably satisfy the relationship "thickness of the second substrate<thickness of the protective substrate for the second barrier layer". By satisfying the above relationship, it is possible to improve the efficiency in forming a barrier layer on a substrate and to easily improve the handleability of the protective film in producing a wavelength conversion sheet.
[0064] The substrate, bulking substrate and protective substrate for barrier layer preferably have a total light transmittance according to JIS K7361-1:1997 of 80% or more, more preferably 85% or more, and even more preferably 87% or more.
[0065] The substrate, bulking substrate and protective substrate for a barrier layer may be subjected to a surface treatment or an adhesion enhancing treatment in order to improve adhesion.
[0066] -Adhesive layer- When the first protective film has a first bulky substrate, the first bulky substrate and the first substrate or the first barrier layer are preferably laminated with strong adhesive strength via a first adhesive layer. When the first protective film has a protective substrate for the first barrier layer, the protective substrate for the first barrier layer and the first substrate or the first barrier layer are preferably laminated releasably via a first adhesive layer. When the second protective film has a second bulky substrate, the second bulky substrate and the second substrate or the second barrier layer are preferably laminated with strong adhesive strength via a second adhesive layer. When the second protective film has a protective substrate for the second barrier layer, the protective substrate for the second barrier layer and the second substrate or the second barrier layer are preferably peelably laminated via a second adhesive layer. Hereinafter, when simply referred to as "adhesive layer", it means "first adhesive layer and second adhesive layer".
[0067] In this specification, "peelable" means that the peel strength of the protective substrate for a barrier layer is 1.0 N / 25 mm or less. <Method for measuring peel strength of protective substrate for first barrier layer> Three test pieces of 25 mm x 150 mm are cut out from the first protective film for quantum dots. Using a tensile tester, the peel strength when peeling the protective substrate for the first barrier layer from the first protective film for quantum dots is measured under the following measurement conditions. When the protective substrate for the first barrier layer is peelably laminated via the first adhesive layer, the peel strength when peeling the protective substrate for the first barrier layer and the first adhesive layer from the first protective film for quantum dots is measured. The average value of the measured values of the three test pieces is taken as the peel strength of the protective substrate for the first barrier layer. The tensile tester is preferably a tensile tester specified in JIS B7721:2018. <Peel strength measurement conditions> Measurement temperature: 23℃ ·Tensioning speed: 300mm / min Peeling direction: 180° Chuck distance: 15mm <Method for measuring peel strength of protective substrate for second barrier layer> The peel strength of the protective substrate for the second barrier layer is measured in the same manner as in the measurement of the peel strength of the protective substrate for the first barrier layer, except that three test pieces are cut out from the second protective film for quantum dots.
[0068] Examples of adhesives constituting the adhesive layer include moisture-curing adhesives, heat-curing adhesives, ultraviolet-curing adhesives, heat-sensitive adhesives (e.g., hot-melt adhesives), pressure-sensitive adhesives, etc. As these various adhesives, general-purpose adhesives can be used.
[0069] In order to make the protective substrate for the barrier layer and the adhesive layer peelable from the substrate or the barrier layer, it is preferable to use an adhesive layer having a weak adhesive strength as the adhesive layer, and it is more preferable to use a pressure-sensitive adhesive layer having a weak adhesive strength.
[0070] The adhesive layer for laminating the bulky base material is preferably a layer formed from a curing adhesive, so as to facilitate good adhesion over a long period of time. Examples of the curing adhesive include moisture-curing adhesives, heat-curing adhesives, and ultraviolet-curing adhesives, among which heat-curing adhesives and ultraviolet-curing adhesives are preferred, and heat-curing adhesives are more preferred.
[0071] Examples of the thermosetting adhesive include general-purpose one-component curing adhesives and two-component curing adhesives. Among these, two-component curing polyurethane adhesives are preferred. The two-component curing polyurethane adhesive is an adhesive containing a polyol compound and an isocyanate compound.
[0072] The thickness of the adhesive layer is preferably from 2 μm to 30 μm, more preferably from 3 μm to 20 μm, and even more preferably from 4 μm to 10 μm.
[0073] -Barrier layer- The first protective film has a first barrier layer, and the second protective film has a second barrier layer. The first barrier layer is preferably located between the first substrate and the first primer layer, and the second barrier layer is preferably located between the second substrate and the second primer layer. When the first protective film has a first bulking substrate, the first barrier layer is preferably located between the first substrate and the first bulking substrate. When the first protective film has a protective substrate for the first barrier layer, the first barrier layer is preferably located between the first substrate and the protective substrate for the first barrier layer. When the second protective film has a second bulking substrate, the second barrier layer is preferably located between the second substrate and the second bulking substrate. When the second protective film has a protective substrate for the second barrier layer, the second barrier layer is preferably located between the second substrate and the protective substrate for the second barrier layer. Hereinafter, when the term "barrier layer" is used simply, it means "first barrier layer and second barrier layer".
[0074] Examples of the barrier layer include a single layer of a single type selected from the group consisting of "an inorganic oxide layer formed by vapor deposition of an inorganic oxide," "a coating layer formed by applying a coating agent containing a water-soluble polymer such as polyvinyl alcohol," and "a layer containing a reaction product of a composition containing a metal oxide and a phosphorus compound," a layer in which a single type selected from the group is laminated, and a layer in which two or more types selected from the group are laminated. Among these, a laminate of an inorganic oxide layer and a coating layer is preferred. That is, the first barrier layer and the second barrier layer preferably include an inorganic oxide layer and a coating layer. Examples of layers containing a reactant of a composition containing a metal oxide and a phosphorus compound include the layers described in WO 2011 / 122036. Hereinafter, embodiments of the inorganic oxide layer and the coating layer will be described.
[0075] When the first barrier layer on the first substrate has an inorganic oxide layer and a coating layer, it preferably has the first substrate, the inorganic oxide layer and the coating layer in this order. When the second barrier layer on the second substrate has an inorganic oxide layer and a coating layer, it preferably has the second substrate, the inorganic oxide layer and the coating layer in this order.
[0076] To improve the barrier properties, the barrier layer preferably has an inorganic oxide layer A, a coating layer A, an inorganic oxide layer B, and a coating layer B in this order. When the barrier layer on the first substrate has the above-mentioned configuration, it preferably has a first substrate, an inorganic oxide layer A, a coating layer A, an inorganic oxide layer B, and a coating layer B in this order. When the barrier layer on the second substrate has the above-mentioned configuration, it preferably has a second substrate, an inorganic oxide layer A, a coating layer A, an inorganic oxide layer B, and a coating layer B in this order.
[0077] - Inorganic oxide layer - The inorganic oxide constituting the inorganic oxide layer may be one or more selected from aluminum oxide, silicon oxide, and magnesium oxide. In order to provide the wavelength conversion sheet with sufficient barrier properties and to improve the production efficiency of the wavelength conversion sheet, aluminum oxide or silicon oxide is preferred. Aluminum oxide, which has excellent transparency, is more preferred.
[0078] The inorganic oxide layer can be formed by, for example, physical vapor deposition (PVD) methods such as vacuum deposition, sputtering, and ion plating, or chemical vapor deposition (CVD) methods such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition. Among these, the vacuum deposition method is preferred because of its high deposition rate and excellent productivity. The PVD method is preferred because carbon is less likely to be mixed into the inorganic oxide layer than the CVD method.
[0079] When the inorganic oxide layer contains silicon and oxygen, the total content of silicon and oxygen in each layer is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more. Examples of inorganic oxides containing silicon and oxygen include silicon oxides (SiOx) such as silicon dioxide. When the inorganic oxide layer contains aluminum and oxygen, the total content of aluminum and oxygen in each layer is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. The inorganic oxide containing aluminum and oxygen may be aluminum oxide (AlOx) such as Al2O3. As long as the effect of the present disclosure is not impaired, a small amount of aluminum hydroxide may be contained as the inorganic oxide containing aluminum and oxygen.
[0080] The preferred thickness of the inorganic oxide layer varies depending on the type of inorganic oxide, and therefore cannot be generalized. When the inorganic oxide layer contains silicon and oxygen, the thickness of the inorganic oxide layer is preferably 15 nm or more, more preferably 20 nm or more, and even more preferably 30 nm or more, in order to improve the barrier property. In addition, when the inorganic oxide layer contains silicon and oxygen, the thickness of the inorganic oxide layer is preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 100 nm or less. By making the thickness 200 nm or less, it is possible to easily prevent scratches and cracks from occurring in the inorganic oxide layer and to easily suppress the color originating from silicon oxide.
[0081] When the inorganic oxide layer contains aluminum and oxygen, the thickness of the inorganic oxide layer is preferably 6 nm or more, and more preferably 7 nm or more, in order to obtain good barrier properties. In addition, when the inorganic oxide layer contains aluminum and oxygen, the thickness of the inorganic oxide layer is preferably 25 nm or less, more preferably 20 nm or less, more preferably 15 nm or less, more preferably 12 nm or less, and more preferably 10 nm or less. By making the thickness 25 nm or less, it is possible to easily suppress the occurrence of scratches and cracks in the inorganic oxide layer.
[0082] An anchor layer may be provided between the inorganic oxide layer and the first substrate or the second substrate in order to improve adhesion.
[0083] -Coating layer- The coating layer preferably contains one or more selected from a water-soluble polymer and a metal alkoxide-based compound. Of the water-soluble polymer and the metal alkoxide-based compound, the coating layer more preferably contains one or more selected from the water-soluble polymer, and further preferably contains one or more selected from the water-soluble polymer and one or more selected from the metal alkoxide-based compound. When the barrier layer has the inorganic oxide layer and the coating layer, the barrier property of the wavelength conversion sheet can be easily improved.
[0084] Examples of the water-soluble polymer include polyvinyl alcohol, polyvinylpyrrolidone, and ethylene-vinyl alcohol copolymer, and among these, polyvinyl alcohol and ethylene-vinyl alcohol copolymer are preferred from the viewpoint of barrier properties, and polyvinyl alcohol is more preferred. That is, the coating layer preferably contains one or more selected from polyvinyl alcohol and ethylene-vinyl alcohol copolymer, and more preferably contains polyvinyl alcohol.
[0085] When the coating layer contains a water-soluble polymer and a metal alkoxide-based compound, the content of the water-soluble polymer per 100 parts by mass of the total amount of the metal alkoxide-based compounds is preferably 5 parts by mass or more and 500 parts by mass or less, more preferably 7 parts by mass or more and 100 parts by mass or less, and even more preferably 8 parts by mass or more and 50 parts by mass or less.
[0086] Examples of the metal alkoxide-based compound include metal alkoxides, metal alkoxide hydrolysates, and metal alkoxide polymers. Metal alkoxides are M(OR) n It is a compound represented by the general formula: In the formula, M represents a metal such as Si, Ti, Al, or Zr, and R represents an alkyl group such as a methyl group or an ethyl group. Specific examples of metal alkoxides include tetramethoxysilane, tetraethoxysilane, and isopropoxyaluminum.
[0087] The coating layer can be formed, for example, by applying a coating liquid containing components constituting the coating layer onto the inorganic oxide layer and drying the coating liquid. The coating liquid may contain additives such as a silane coupling agent, a curing agent, and a dispersing agent.
[0088] In order to provide good barrier properties, the thickness of the coating layer is preferably 70 nm or more, more preferably 100 nm or more, and even more preferably 150 nm or more. The thickness of the coating layer is preferably 600 nm or less, more preferably 480 nm or less, more preferably 370 nm or less, and even more preferably 300 nm or less. By making the thickness 600 nm or less, the wavelength conversion sheet can be made thin and the occurrence of cracks in the coating layer can be easily suppressed.
[0089] -Primer layer- The first protective film has a first primer layer to improve adhesion to the quantum dot-containing layer, and the second protective film has a second primer layer to improve adhesion to the quantum dot-containing layer. The first primer layer and the second primer layer are each disposed so as to be in contact with the quantum dot-containing layer. Therefore, the first primer layer is preferably located as the outermost layer on one side of the first protective film. Also, the second primer layer is preferably located as the outermost layer on one side of the second protective film. Hereinafter, when the term "primer layer" is used simply, it means "the first primer layer and the second primer layer".
[0090] The primer layer preferably contains a resin component. Examples of the resin component include polyester resin, polyurethane resin, and acrylic resin. Among these, polyurethane resin is preferable, and polyester polyurethane resin is more preferable. That is, the primer layer preferably contains a polyurethane resin, and more preferably contains a polyester polyurethane resin. Polyurethane-based resins such as polyester polyurethane-based resins tend to provide good adhesion to the quantum dot-containing layer, and can also ease the stress that occurs when the quantum dot-containing layer is cured with ionizing radiation or thermally cured, making it easier to suppress the stress from being transmitted to the first protective film and the second protective film.
[0091] The polyurethane resin may be a one- or two-liquid type polyurethane resin composition obtained by reacting a polyfunctional isocyanate with a hydroxyl group-containing compound. The polyfunctional isocyanate and the hydroxyl group-containing compound may each be used alone or in combination. Examples of the polyfunctional isocyanate include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, and polymethylene polyphenylene polyisocyanate, and aliphatic polyisocyanates such as hexamethylene diisocyanate and isophorone diisocyanate. Examples of the hydroxyl group-containing compound include polyether polyol, polyester polyol, polyester polyurethane polyol, and polyacrylate polyol. In the present disclosure, polyester polyol is particularly preferred from the viewpoints of adhesion to the quantum dot-containing layer and durability. The reaction product of polyester polyol and polyfunctional isocyanate becomes a polyester polyurethane resin.
[0092] The content of the polyurethane resin is preferably 50% by mass or more, and more preferably 70% by mass or more, based on the total amount of the primer layer.
[0093] In order to improve durability, the primer layer is preferably a layer containing a cured product of a curable resin composition. Examples of the cured product of the curable resin composition include the reaction product of the one- or two-liquid type polyurethane resin composition described above.
[0094] The primer layer may contain a silane coupling agent. The silane coupling agent forms a silanol group (Si-OH) by hydrolysis of a functional group such as a chloro group, an alkoxy group, or an acetoxy group at one end of the molecule. This modifies the resin composition of the primer layer by a covalent bond or the like to form a strong bond. In addition, the organic functional group such as a vinyl group, a methacryloxy group, an amino group, an epoxy group, or a mercapto group at the other end of the silane coupling agent can easily improve the adhesion between the primer layer and the quantum dot-containing layer.
[0095] Examples of silane coupling agents include γ-chloropropyltrimethoxysilane, vinyltrichlorosilane, vinyltriethoxysilane, vinyl-tris(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, vinyltriacetoxysilane, γ-mercaptopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-ureidopropyltriethoxysilane, bis(β-hydroxyethyl)-γ-aminopropyltriethoxysilane, and γ-aminopropylsilicone. One or more of these may be used.
[0096] The content of the silane coupling agent is preferably 1% by mass or more, more preferably 3% by mass or more, based on the total amount of the primer layer. When the content of the silane coupling agent is in the above range, the adhesion between the primer layer and the quantum dot-containing layer can be further improved. In order to improve the extensibility of the primer layer and to suppress the occurrence of cracks in the primer layer, the content of the silane coupling agent is preferably 30 mass% or less, and more preferably 20 mass% or less, based on the total amount of the primer layer.
[0097] The primer layer may further contain a filler. The filler has a role of adjusting the viscosity of the coating liquid for forming the primer layer and improving the coating suitability. Examples of the filler that can be used include calcium carbonate, barium sulfate, alumina white, silica, talc, glass frit, and resin powder.
[0098] The primer layer may further contain additives such as a stabilizer, a crosslinking agent, a lubricant, and an ultraviolet absorber, if necessary.
[0099] The thickness of the primer layer is preferably at least 100 nm, more preferably at least 150 nm, and even more preferably at least 200 nm, and is preferably at most 500 nm, more preferably at most 400 nm, and even more preferably at most 300 nm. By making the thickness 100 nm or more, it is possible to easily improve the adhesion between the primer layer and the quantum dot-containing layer, and by making the thickness 500 nm or less, it is possible to suppress the absorption of transmitted light by the primer layer and improve the brightness of the backlight using the wavelength conversion sheet.
[0100] -Anti-sticking layer- The first protective film may have a first anti-sticking layer. The first anti-sticking layer is preferably located as the outermost layer of the first protective film on the side opposite to the first primer layer. The second protective film may have a second anti-sticking layer. The second anti-sticking layer is preferably located as the outermost layer of the second protective film on the side opposite to the second primer layer. Hereinafter, when the term "anti-sticking layer" is used simply, it means "the first anti-sticking layer and the second anti-sticking layer".
[0101] The anti-sticking layer can prevent blocking from occurring in the wavelength-conversion sheet wound into a roll, and can also prevent damage caused by rubbing between the wavelength-conversion sheet and other members when the wavelength-conversion sheet is incorporated into a liquid crystal display device. The anti-sticking layer preferably contains a binder resin and a filler for preventing sticking.
[0102] Physical Properties The first and second protective films have a water vapor permeability of 0.20 g / m according to JIS K7129-2:2019. 2 ·day or less, and 0.15 g / m 2 The temperature and relative humidity when measuring the water vapor transmission rate are different from the conditions 1 to 5 in JIS Table 1. Specifically, the temperature is 40° C. and the relative humidity is 100%.
[0103] The first and second protective films have an oxygen permeability of 0.5cc / m according to JIS K7126-2:2006. 2 ·day·atm or less. The temperature and relative humidity when measuring the oxygen permeability are different from those in JIS Table 1. Specifically, the temperature is 23°C and the relative humidity is 90%.
[0104] The first protective film and the second protective film preferably have a total light transmittance according to JIS K7361-1:1997 of 80% or more, more preferably 85% or more, and even more preferably 87% or more.
[0105] <Quantum dot-containing layer> The quantum dot-containing layer contains quantum dots and a binder resin. In order to improve durability, the binder resin preferably contains a cured product of a curable resin composition, and more preferably contains a cured product of an ultraviolet curable resin composition. That is, the quantum dot-containing layer is preferably a layer containing a cured product of a curable resin composition, and more preferably a layer containing a cured product of an ultraviolet curable resin composition. In order to improve durability, the quantum dot-containing layer preferably contains 50% by mass or more, and more preferably 70% by mass or more, of the cured product of the curable resin composition relative to the total amount of components constituting the quantum dot-containing layer.
[0106] Quantum dots are nanometer-sized semiconductor particles that exhibit unique optical and electrical properties due to the quantum confinement effect (quantum size effect) in which electrons and excitons are confined within tiny nanometer-sized crystals. Quantum dots are also called semiconductor nanoparticles and semiconductor nanocrystals. Quantum dots are nanometer-sized semiconductor particles that are not particularly limited as long as they are made of a material that produces a quantum confinement effect. Examples of quantum dots include semiconductor particles whose emission color is regulated by their own particle size and semiconductor particles having a dopant.
[0107] For example, in the case of a quantum dot consisting only of a core made of CdSe, the peak wavelengths of the fluorescence spectrum are 528 nm, 570 nm, 592 nm, and 637 nm when the particle size is 2.3 nm, 3.0 nm, 3.8 nm, and 4.6 nm. In other words, the particle size of a quantum dot that emits secondary light with a peak wavelength of 637 nm is 4.6 nm, and the particle size of a quantum dot that emits secondary light with a peak wavelength of 528 nm is 2.3 nm. The quantum dots preferably include one or more types selected from quantum dots that emit secondary light of a wavelength corresponding to red and quantum dots that emit secondary light of a wavelength corresponding to green, and more preferably include quantum dots that emit secondary light of a wavelength corresponding to red and quantum dots that emit secondary light of a wavelength corresponding to green. The quantum dots may include quantum dots other than the quantum dots that emit secondary light of a wavelength corresponding to red and the quantum dots that emit secondary light of a wavelength corresponding to green.
[0108] The content of the quantum dots is appropriately adjusted depending on the thickness of the quantum dot-containing layer, the recycling rate of light in the backlight, the desired color tone, etc. If the thickness of the quantum dot-containing layer is within the range described below, the content of the quantum dots is preferably 0.010 parts by mass or more and 1.0 parts by mass or less with respect to 100 parts by mass of the binder resin of the quantum dot-containing layer.
[0109] Specific examples of the core material of the quantum dot include II-VI group semiconductor compounds such as MgS, MgSe, MgTe, CaS, CaSe, CaTe, SrS, SrSe, SrTe, BaS, BaSe, BaTe, ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, HgS, HgSe and HgTe, III-V group semiconductor compounds such as AlN, AlP, AlAs, AlSb, GaAs, GaP, GaN, GaSb, InN, InAs, InP, InSb, TiN, TiP, TiAs and TiSb, and IV group semiconductors such as Si, Ge and Pb. Semiconductor crystals containing semiconductor compounds containing three or more elements such as InGaP can also be used. Furthermore, as a quantum dot consisting of semiconductor particles having a dopant, the above semiconductor compound may be added with Eu 3+ , Tb 3+ , Ag + , Cu + It is also possible to use a semiconductor crystal doped with a rare earth metal cation or a transition metal cation such as the following. As the core material of the quantum dot, from the viewpoints of ease of preparation, controllability of particle size for obtaining light emission in the visible range, and fluorescence quantum yield, semiconductor crystals such as CdS, CdSe, CdTe, InP, and InGaP are suitable.
[0110] The quantum dots may be composed of one type of semiconductor compound or two or more types of semiconductor compounds, and may have, for example, a core-shell structure having a core composed of a semiconductor compound and a shell composed of a semiconductor compound different from the core. When using core-shell quantum dots, the semiconductor constituting the shell can be made of a material with a higher band gap than the semiconductor compound constituting the core, so that excitons are confined in the core, thereby increasing the luminous efficiency of the quantum dots. Examples of core-shell structures (core / shell) having such a band gap relationship include CdSe / ZnS, CdSe / ZnSe, CdSe / CdS, CdTe / CdS, InP / ZnS, GaP / ZnS, Si / ZnS, InN / GaN, InP / CdSSe, InP / ZnSeTe, InGaP / ZnSe, InGaP / ZnS, Si / AlP, InP / ZnSTe, InGaP / ZnSTe, InGaP / ZnSSe, etc.
[0111] The size of the quantum dots can be appropriately controlled by the material that constitutes the quantum dots so that light of the desired wavelength can be obtained. As the particle size of the quantum dots decreases, the energy band gap increases. In other words, as the crystal size decreases, the emission of the quantum dots shifts to the blue side, that is, to the higher energy side. Therefore, by changing the size of the quantum dots, the emission wavelength can be adjusted over the entire wavelength range of the ultraviolet, visible, and infrared spectrum. In general, the particle size (diameter) of the quantum dots is preferably in the range of 0.5 nm to 20 nm, more preferably in the range of 1 nm to 10 nm. Note that the narrower the size distribution of the quantum dots, the more vivid the emitted light color can be obtained. The shape of the quantum dots is not particularly limited, and may be, for example, spherical, rod-like, disk-like, etc. When the quantum dots are not spherical, the particle size of the quantum dots may be the same as that of a true sphere having the same volume. The quantum dots may be coated with a resin.
[0112] In order to improve durability, the binder resin of the quantum dot-containing layer preferably contains a cured product of a curable resin composition such as a thermosetting resin composition or an ionizing radiation curable resin composition. More preferably, the binder resin of the quantum dot-containing layer contains a cured product of an ultraviolet ray curable resin composition.
[0113] The thermosetting resin composition is a composition containing at least a thermosetting resin, and is a resin composition that is cured by heating. In addition to the thermosetting resin, the thermosetting resin composition preferably contains a thiol compound described below, and more preferably contains a polyfunctional thiol compound. Examples of the thermosetting resin include acrylic resin, urethane resin, phenol resin, urea melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, etc. In the thermosetting resin composition, a curing agent is added to the curable resin as required.
[0114] The ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter also referred to as "ionizing radiation curable compound"). In addition to the ionizing radiation curable compound, the ionizing radiation curable resin composition preferably contains a thiol compound described below, more preferably a polyfunctional thiol compound. The ionizing radiation curable resin composition is preferably an ultraviolet ray curable resin composition.
[0115] Examples of the ionizing radiation curable functional group include ethylenically unsaturated bond groups such as (meth)acryloyl group, vinyl group, and allyl group, as well as epoxy group, oxetanyl group, and the like, among which ethylenically unsaturated bond groups are preferred. Among the ethylenically unsaturated bond groups, (meth)acryloyl group is preferred. Hereinafter, an ionizing radiation curable compound having a (meth)acryloyl group will be referred to as a (meth)acrylate-based compound. In other words, the binder resin preferably contains a cured product of a composition containing a (meth)acrylate-based compound. In this specification, "(meth)acrylate" refers to methacrylate and acrylate. In addition, in this specification, "ionizing radiation" refers to electromagnetic waves or charged particle beams that have an energy quantum capable of polymerizing or crosslinking molecules, and typically ultraviolet rays (UV) or electron beams (EB) are used, but other types of radiation such as electromagnetic waves, such as X-rays and gamma rays, and charged particle beams, such as alpha rays and ion beams, can also be used.
[0116] The ionizing radiation curable compound may be a monofunctional ionizing radiation curable compound having only one of the functional groups, a polyfunctional ionizing radiation curable compound having two or more of the functional groups, or a mixture thereof. Among these, a polyfunctional ionizing radiation curable compound is preferred, and a polyfunctional (meth)acrylate-based compound having two or more (meth)acryloyl groups is more preferred. That is, the binder resin preferably contains a cured product of a polyfunctional ionizing radiation curable compound, and more preferably contains a cured product of a polyfunctional (meth)acrylate-based compound. Furthermore, the binder resin preferably contains a cured product of a composition containing a polyfunctional ionizing radiation curable compound and a thiol compound, and more preferably contains a cured product of a composition containing a polyfunctional (meth)acrylate-based compound and a thiol compound.
[0117] The polyfunctional (meth)acrylate compound may have an alkyleneoxy group. The alkyleneoxy group is, for example, preferably an alkyleneoxy group having 2 or more and 4 carbon atoms, more preferably an alkyleneoxy group having 2 or 3 carbon atoms, and even more preferably an alkyleneoxy group having 2 carbon atoms.
[0118] The polyfunctional (meth)acrylate compound having an alkyleneoxy group may be a polyfunctional (meth)acrylate compound having a polyalkyleneoxy group containing a plurality of alkyleneoxy groups. When the polyfunctional (meth)acrylate compound has an alkyleneoxy group, the number of alkyleneoxy groups in one molecule is preferably 2 to 30, more preferably 2 to 20, even more preferably 3 to 10, and even more preferably 3 to 5.
[0119] When the polyfunctional (meth)acrylate compound has an alkyleneoxy group, it is preferable that the compound has a bisphenol structure. This tends to improve the heat resistance of the cured product. Examples of the bisphenol structure include a bisphenol A structure and a bisphenol F structure, and among them, a bisphenol A structure is preferable. Among the polyfunctional (meth)acrylate compounds having an alkyleneoxy group, ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, and propoxylated ethoxylated bisphenol A di(meth)acrylate are preferred, with ethoxylated bisphenol A di(meth)acrylate being more preferred.
[0120] The ionizing radiation curable compound may be a monomer, an oligomer, a low molecular weight polymer, or a mixture thereof.
[0121] As described above, the heat-curable resin composition and the ionizing radiation-curable resin composition preferably contain a thiol compound. A thiol compound is a compound having one or more units represented by R-SH (R is an organic group). In this specification, a compound having one unit represented by R-SH is called a monofunctional thiol compound, and a compound having two or more units represented by R-SH is called a polyfunctional thiol compound.
[0122] The thiol compound may be a monofunctional thiol compound, but from the viewpoint of improving the strength of the quantum dot-containing layer, a polyfunctional thiol compound is preferable. Among the polyfunctional thiol compounds, a trifunctional thiol compound or a tetrafunctional thiol compound is more preferable.
[0123] In the presence of a radical polymerization initiator, the thiol compound undergoes a thiol-ene reaction with a compound having a radical polymerizable functional group according to the following formula. The thiol-ene reaction can suppress polymerization shrinkage, and therefore is preferable in that it can ease the stress generated during curing of the quantum dot-containing layer, and as a result, it is easier to improve the interlayer adhesion of the wavelength conversion sheet. In addition, the cured product obtained by the thiol-ene reaction is preferable in that it can easily improve heat resistance. The following reaction is an example of a reaction between a monofunctional thiol compound and a compound having one radically polymerizable functional group. It is considered that a reaction product between a polyfunctional thiol compound and a compound having two or more radically polymerizable functional groups is likely to form a dendrimer structure. When a dendrimer structure is formed, it is considered that the flexibility of the quantum dot-containing layer is increased, and the quantum dot-containing layer itself is likely to exhibit excellent stress relaxation properties. Examples of the radically polymerizable functional group include ethylenically unsaturated bond-containing groups such as (meth)acryloyl groups, vinyl groups, and allyl groups.
[0124] [ka] [In the formula, R 1 and R 2 is an organic group.
[0125] Specific examples of monofunctional thiol compounds include hexanethiol, 1-heptanethiol, 1-octanethiol, 1-nonanethiol, 1-decanethiol, 3-mercaptopropionic acid, methyl mercaptopropionate, methoxybutyl mercaptopropionate, octyl mercaptopropionate, tridecyl mercaptopropionate, 2-ethylhexyl-3-mercaptopropionate, and n-octyl-3-mercaptopropionate.
[0126] Specific examples of polyfunctional thiol compounds include ethylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), 1,2-propylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptobutyrate), 1,4-butanediol bis(3-mercaptopropionate), 1,4-butanediol bis(3-mercaptopropionate), captobutyrate), 1,8-octanediol bis(3-mercaptopropionate), 1,8-octanediol bis(3-mercaptobutyrate), hexanediol bisthioglycolate, trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptoisobutyrate), trimethylolpropane tris(2 ... Trimethylolpropane tristhioglycolate, tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, trimethylolethane tris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptoisobutyrate), pentaerythritol tetrakis(2-mercaptoisobutyrate), dipentaerythritol Examples of the erythritol hexakis include erythritol hexakis(3-mercaptopropionate), dipentaerythritol hexakis(2-mercaptopropionate), dipentaerythritol hexakis(3-mercaptobutyrate), dipentaerythritol hexakis(3-mercaptoisobutyrate), dipentaerythritol hexakis(2-mercaptoisobutyrate), pentaerythritol tetrakisthioglycolate, and dipentaerythritol hexakisthioglycolate.
[0127] In the ionizing radiation curable resin composition (or thermosetting resin composition), the mass ratio of the ionizing radiation curable compound (or thermosetting resin) to the thiol compound is preferably 80:20 to 35:65, and more preferably 70:30 to 40:60.
[0128] When the ionizing radiation curable compound is an ultraviolet ray curable compound, the ionizing radiation curable composition preferably contains additives such as a photopolymerization initiator and a photopolymerization accelerator.
[0129] The quantum dot containing layer may also include internal diffusing particles, such as organic and inorganic particles. The content of the internal diffusion particles is preferably 1 part by mass or more and 40 parts by mass or less, and more preferably 3 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the binder resin. The average particle size of the internal diffusion particles is preferably 1 μm or more and 7 μm or less, and more preferably 1 μm or more and 3 μm or less.
[0130] The thickness of the quantum dot-containing layer is preferably from 10 μm to 200 μm, more preferably from 20 μm to 150 μm, and even more preferably from 30 μm to 100 μm. The method for producing a wavelength conversion sheet according to the present disclosure can easily suppress curling even if the quantum dot-containing layer is thick.
[0131] <Application> The wavelength conversion sheet obtained by the manufacturing method of the present disclosure can be used, for example, as a surface light source. Examples of surface light sources include a backlight source for a liquid crystal display device, a backlight source for an inspection device, and the like. That is, the wavelength conversion sheet of the present disclosure can be used as a "wavelength conversion sheet for a backlight source for a liquid crystal display device", a "wavelength conversion sheet for a backlight source for an inspection device", and the like. Furthermore, the wavelength conversion sheet obtained by the manufacturing method of the present disclosure can also be used as a "horticultural wavelength conversion sheet". Examples of horticultural wavelength conversion sheets include sheets that have the function of converting ultraviolet light into wavelengths suitable for plant growth. Examples of wavelengths suitable for plant growth include wavelengths suitable for photosynthesis. Horticultural wavelength conversion sheets can be installed on the ceilings of horticultural facilities such as vinyl greenhouses and glass rooms.
[0132] This disclosure includes the following [1] to [5]. [1] A method for producing a wavelength conversion sheet, comprising the following steps 1 to 4: Step 1: A step of forming a quantum dot-containing layer by applying a coating liquid for forming a quantum dot-containing layer onto a first primer layer of a first protective film for quantum dots, the first primer layer having at least a first primer layer, a first substrate, and a first barrier layer. Step 2: Irradiating the quantum dot-containing layer with ultraviolet light for the first time. Step 3: A step of obtaining a work-in-progress wavelength conversion sheet having, in this order, the first protective film for quantum dots, the quantum dot-containing layer, and the second protective film for quantum dots, by bonding the surface of the second primer layer side of the second protective film for quantum dots, which has at least a second primer layer, a second substrate, and a second barrier layer, to the quantum dot-containing layer. Step 4: A step of irradiating the quantum dot-containing layer of the in-process product with ultraviolet light for a second time, with the proviso that the relationship of the integrated amount of ultraviolet light for the first time < the integrated amount of ultraviolet light for the second time is satisfied. [2] The method for producing a wavelength conversion sheet according to [1], wherein the coating liquid for forming a quantum dot-containing layer contains an ultraviolet-curable resin composition. [3] The method for producing a wavelength conversion sheet according to [1] or [2], wherein the first protective film for quantum dots further has a protective substrate for a first barrier layer, and the method comprises, after step 4, a step of peeling off the protective substrate for the first barrier layer. [4] The method for producing a wavelength conversion sheet according to any one of [1] to [3], wherein the ratio of the accumulated light amount of the second ultraviolet ray to the accumulated light amount of the first ultraviolet ray is 2 or more and 30 or less. [5] The method for producing a wavelength conversion sheet according to any one of [1] to [4], wherein the first barrier layer and the second barrier layer include an inorganic oxide layer and a coating layer. EXAMPLES
[0133] Next, the present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited to these examples. In addition, "parts" and "%" are based on mass unless otherwise specified.
[0134] 1. Measurement and Evaluation The wavelength conversion sheets of the examples and comparative examples were subjected to the following measurements and evaluations. The results are shown in Table 1.
[0135] 1-1. Curl According to the procedures of X1 to X4 in the specification, the curl of the wavelength conversion sheets of the examples and comparative examples was measured. Since the wavelength conversion sheets of the examples and comparative examples were curled so that the first protective film side was convex, only Ave1 was measured and Ave1 was taken as Ave(max). Based on the Ave(max) value, the sheets were ranked as follows: AA: Ave(max) is 5.0mm or less A: Ave(max) is greater than 5.0mm and less than 7.5mm A - : Ave(max) is over 7.5mm and 10.0mm or less B: Ave(max) is greater than 10.0mm and less than 15.0mm C: Ave(max) is over 15.0mm
[0136] 2. Preparation of Quantum Dot Dispersion In a glove box purged with nitrogen so that the oxygen concentration was 300 ppm or less, quantum dots and amino-modified silicone were mixed in the composition ratio shown below, and stirred for 4 hours with a magnetic stirrer while being heated in a water bath at 90° C. After that, the mixture was filtered through a polypropylene filter with a pore size of 0.2 μm to obtain a CdSe / ZnS core-shell quantum dot dispersion. Quantum dots 0.9 parts by weight (Emission peak: 540 nm, serial number: 748056, Sigma-Aldrich) Quantum dots 0.9 parts by weight (Emission peak: 630 nm, serial number: 790206, Sigma-Aldrich) Amino-modified silicone 99 parts by weight (Genesee, product number: GP-344, viscosity: 670 mPa s)
[0137] 3. Preparation of wavelength conversion sheet [Example 1] <First protective film> The surface of the first substrate (biaxially oriented PET film having an easy-adhesion layer on one side, thickness: 12 μm, "Embret (registered trademark) PTM" of Unitika Co., Ltd.) that does not have an easy-adhesion layer was subjected to plasma treatment in a vacuum deposition apparatus, and then aluminum oxide was deposited in-line by a vacuum deposition method to form an inorganic oxide layer A having a thickness of 8 nm. Next, the following coating layer forming coating liquid was applied on the inorganic oxide layer A by gravure printing, and heat-treated at 180 ° C. for 60 seconds to form a coating layer B having a thickness of 200 nm. Next, aluminum oxide was deposited on the coating layer B by a vacuum deposition method to form an inorganic oxide layer C having a thickness of 8 nm. Next, the following coating layer forming coating liquid was applied on the inorganic oxide layer C by gravure printing, and heat-treated at 180 ° C. for 60 seconds to form a coating layer D having a thickness of 230 nm. Next, the following primer layer-forming coating solution was applied onto the coating layer D by gravure printing, and heat-treated at 80° C. for 60 seconds to form a first primer layer having a thickness of 250 nm. By the above operations, a laminate 1-1 having a first primer layer, a first barrier layer, and a first substrate in this order was obtained. The first barrier layer has, from the first substrate side, an inorganic oxide layer A, a coating layer B, an inorganic oxide layer C, and a coating layer D in this order. Furthermore, by the above operations, a first protective film used in Example 1 having a first primer layer, a first barrier layer, and a first substrate in this order was obtained. The total thickness T1 of the first protective film used in Example 1 was 12.696 μm.
[0138] <Second protective film> The laminate 1-1 was used as the second protective film in Example 1. The second protective film had a second primer layer, a second barrier layer, and a second substrate in this order. The total thickness T2 of the second protective film used in Example 1 was 12.696 μm.
[0139] <Preparation of wavelength conversion sheet> A quantum dot-containing layer coating solution 1 having the following formulation was applied to the surface of the first primer layer side of the first protective film, dried, and then irradiated with ultraviolet light to form a quantum dot-containing layer, thereby obtaining a laminate 1-2 having a quantum dot-containing layer on the first primer layer of the first protective film. The first ultraviolet light was irradiated from the quantum dot-containing layer side. The integrated light intensity of the first ultraviolet light was 100 mJ / cm2. 2 It was decided. Next, the surface of the quantum dot-containing layer of the laminate 1-2 was laminated against the surface of the second primer layer of the second protective film, and then ultraviolet light was irradiated to obtain the wavelength conversion sheet of Example 1. The thickness T3 of the quantum dot-containing layer was 50 μm. The second ultraviolet light was irradiated from the second protective film side. The cumulative light amount of the second ultraviolet light was 600 mJ / cm2. 2 It was decided.
[0140] <Preparation of Coating Solution for Forming Covering Layer> Tetraethoxysilane was mixed into a solution (pH 2.2) of water, isopropyl alcohol, and 0.5N hydrochloric acid while cooling to 10°C to prepare solution A. Separately, solution B was prepared by mixing polyvinyl alcohol with a saponification value of 99% or more and isopropyl alcohol. Solution A and solution B were mixed to prepare a coating liquid for forming a coating layer (solid content: 5% by mass). In the coating liquid for forming a coating layer, the mass ratio of tetraethoxysilane to polyvinyl alcohol was 100:14.
[0141] <Coating solution for forming primer layer> Polyester polyol 50 parts by weight (Hydroxyl value: 62 mg KOH / g, solid content: 20% by mass) Silane coupling agent 1 part by weight (3-Glycidoxypropylmethyldimethoxysilane) Silica filler 1 part by weight (Average particle size 5μm) Hardener 1 part by weight (1,6-hexamethylene diisocyanate, solid content 35% by mass) Solvent 50 parts by weight (Methyl ethyl ketone)
[0142] <Quantum dot-containing layer coating solution 1> Multifunctional acrylate compound 58.11 parts by weight (Ethoxylated bisphenol A diacrylate; Shin-Nakamura Chemical Co., Ltd.'s product name "ABE-300") Polyfunctional thiol compound 38.74 parts by mass (Pentaerythritol tetrakis(3-mercaptopropionate); trade name "PEMP" from SC Organic Chemicals) Photopolymerization initiator 0.5 parts by weight (IGM Resins BV's product name: "Omnirad TPO H") 1.61 parts by weight of the quantum dot dispersion liquid prepared in "2" above Acetic acid 0.79 parts by weight Titanium oxide 0.25 parts by weight (Chemours' product name "Typure R-706"; particle size 0.36 μm)
[0143] [Example 2] A wavelength conversion sheet of Example 2 was obtained in the same manner as in Example 1, except that the thickness of the first substrate was changed to 23 μm and the thickness T3 of the quantum dot-containing layer was changed to 70 μm. The total thickness T1 of the first protective film used in Example 2 was 23.696 μm. The total thickness T2 of the second protective film used in Example 2 was 23.696 μm.
[0144] [Comparative Example 1] A wavelength conversion sheet of Comparative Example 1 was obtained in the same manner as in Example 1, except that the first ultraviolet ray irradiation was not performed and the integrated light amount of the second ultraviolet ray irradiation was changed to the value in Table 1.
[0145] [Comparative Example 2] A wavelength conversion sheet of Comparative Example 2 was obtained in the same manner as in Example 1, except that the first ultraviolet ray irradiation was not performed and the integrated light amount of the second ultraviolet ray irradiation was changed to the value in Table 1.
[0146] [Example 3] A wavelength conversion sheet of Example 3 was obtained in the same manner as in Example 1, except that the quantum dot-containing layer coating liquid 1 was changed to the quantum dot-containing layer coating liquid 2 described below.
[0147] <Quantum dot-containing layer coating solution 2> Multifunctional acrylate compound 58.11 parts by weight (Ethoxylated bisphenol A diacrylate; Shin-Nakamura Chemical Co., Ltd.'s product name "ABE-300") Photopolymerization initiator 3.0 parts by weight (IGM Resins BV's product name: "Omnirad TPO H") 1.61 parts by weight of the quantum dot dispersion liquid prepared in "2" above Acetic acid 0.79 parts by weight Titanium oxide 0.25 parts by weight (Chemours' product name "Typure R-706"; particle size 0.36 μm)
[0148] [Comparative Example 3] A wavelength conversion sheet of Comparative Example 3 was obtained in the same manner as in Comparative Example 1, except that the quantum dot-containing layer coating liquid 1 was changed to the quantum dot-containing layer coating liquid 2 described above.
[0149] [Example 4] <First protective film> The laminate 1-1 was used as a first protective film in Example 4. The first protective film had a first primer layer, a first barrier layer, and a first substrate in this order.
[0150] <Second protective film> An inorganic oxide layer A, a coating layer B, an inorganic oxide layer C, and a coating layer D were formed on the side of the second substrate (biaxially oriented PET film having an easy-adhesion layer on one side, thickness: 12 μm) that did not have an easy-adhesion layer in the same manner as the laminate 1-1. Next, the primer layer-forming coating liquid was applied by gravure printing to the surface of the second substrate on which the easy-adhesion layer was formed, and the coating liquid was heat-treated at 80° C. for 60 seconds to form a second primer layer having a thickness of 250 nm. By the above operations, a laminate 1-3 having a second primer layer, a second substrate, and a second barrier layer in this order was obtained. The second barrier layer has, from the second substrate side, an inorganic oxide layer A, a coating layer B, an inorganic oxide layer C, and a coating layer D in this order. The laminate 1-3 was used as a second protective film in Example 4. The total thickness T1 of the first protective film and the total thickness T2 of the second protective film used in Example 4 were both 12.696 μm.
[0151] <Preparation of wavelength conversion sheet> The quantum dot-containing layer coating solution 1 having the above-mentioned formulation was applied to the surface of the first primer layer side of the first protective film, dried, and then irradiated with ultraviolet light to form a quantum dot-containing layer, thereby obtaining a laminate 1-4 having a quantum dot-containing layer on the first primer layer of the first protective film. The first ultraviolet light was irradiated from the quantum dot-containing layer side. The integrated light intensity of the first ultraviolet light was 100 mJ / cm. 2 It was decided. Next, the quantum dot-containing layer side of the laminate 1-4 was laminated to face the second primer layer side of the second protective film, and ultraviolet rays were irradiated to obtain the wavelength conversion sheet of Example 4. The quantum dot-containing layer had a thickness T3 of 50 μm. The second ultraviolet rays were irradiated from the second protective film side. The cumulative light amount of the second ultraviolet rays was 600 mJ / cm. 2 In the wavelength conversion sheet of Example 4, the layers constituting the first protective film and the layers constituting the second protective film are arranged asymmetrically with respect to the quantum dot-containing layer. The wavelength conversion sheet of Example 4 is different from the wavelength conversion sheet of Example 1 in the layer structure of the second protective film. (The second protective film of Example 4 has a second primer layer, a second substrate, and a second barrier layer in this order. On the other hand, the second protective film of Example 1 has a second primer layer, a second barrier layer, and a second substrate in this order.)
[0152] [Table 1]
[0153] From the results in Table 1, it can be confirmed that the manufacturing method of the wavelength conversion sheet of the example can suppress curling of the wavelength conversion sheet. [Explanation of symbols]
[0154] 10: First protective film for quantum dots 11: First primer layer 12: First base material 13: First barrier layer 14: First adhesive layer 15: Protective substrate for first barrier layer 20: Second protective film for quantum dots 21: Second primer layer 22:Second base material 23: Second barrier layer 30: Quantum dot-containing layer 200: Wavelength conversion sheet 201: Sample made from wavelength conversion sheet 500: Level platform
Claims
1. A method for producing a wavelength conversion sheet, comprising the following steps 1 to 4: Step 1: A step of forming a quantum dot-containing layer by applying a coating liquid for forming a quantum dot-containing layer onto the first primer layer of a first protective film for quantum dots, the first primer layer having at least a first primer layer, a first substrate, and a first barrier layer. Step 2: Irradiating the quantum dot-containing layer with ultraviolet light for the first time. Step 3: A step of obtaining a work-in-progress wavelength conversion sheet having, in this order, the first protective film for quantum dots, the quantum dot-containing layer, and the second protective film for quantum dots, by bonding the surface of the second primer layer side of the second protective film for quantum dots, which has at least a second primer layer, a second substrate, and a second barrier layer, to the quantum dot-containing layer. Step 4: A step of irradiating the quantum dot-containing layer of the in-process product with ultraviolet light for a second time, with the proviso that the relationship of the integrated amount of ultraviolet light for the first time < the integrated amount of ultraviolet light for the second time is satisfied.
2. The method for producing a wavelength conversion sheet according to claim 1 , wherein the coating liquid for forming a quantum dot-containing layer contains an ultraviolet-curable resin composition.
3. 2. The method for producing a wavelength conversion sheet according to claim 1, wherein the first protective film for quantum dots further has a protective substrate for a first barrier layer, and the method further comprises a step of peeling off the protective substrate for the first barrier layer after step 4.
4. 2 . The method for producing a wavelength conversion sheet according to claim 1 , wherein the ratio of an integrated light amount of the second ultraviolet ray to an integrated light amount of the first ultraviolet ray is 2 or more and 30 or less.
5. The method for producing a wavelength conversion sheet according to claim 1 , wherein the first barrier layer and the second barrier layer include an inorganic oxide layer and a coating layer.
Citation Information
Patent Citations
Radiation-sensitive resin composition, cured film, light-emitting element, wavelength conversion film, and method for forming light-emitting layer
JP2015018131A
Fluorescent film and display film
WO2012132239A1
Barrier film, and wavelength conversion sheet, back light, and liquid crystal display device which use same
WO2022039013A1
Barrier film, wavelength conversion sheet using same, backlight and liquid cyrstal display device
WO2022039015A1